Factors affecting the implementation of environmental management accounting - A study of manufacturing enterprises - Nu, Tran The; Chi, Bui Linh; Bac, Dang Thi; Huong, Hoang Dinh; Hai, Nguyen Thi Thanh (Edelweiss Applied Science and Technology, 2025)
Environmental Management Accounting (EMA) plays a crucial role in helping businesses manage and reduce the environmental impacts of their production activities. The aim of this study is to measure and analyze the factors influencing the implementation of EMA in manufacturing enterprises in Hanoi City, Vietnam. We use both qualitative and quantitative research methods. The research sample consisted of 163 accountants, chief accountants, and other related personnel in manufacturing enterprises (MEs) in Hanoi. Based on contingency theory, institutional theory, and stakeholder theory, the study evaluates the impact of business size, regulatory pressure, stakeholder pressure, the competency of accounting staff, and managerial awareness on the adoption of EMA. The results show that business size, regulatory pressure, and managerial awareness positively affect the implementation of EMA. Larger enterprises, with more financial and human resources, are more likely to implement EMA effectively. Additionally, the study reveals that pressure from stakeholders and difficulties in collecting environmental data are significant factors. These findings provide valuable insights for businesses and policymakers in promoting environmental accounting in Vietnam.